The meaning of pseudonyms in selected Zimbabwean online newspapers - Nhongo, Raphael (National Inquiry Services Centre, 2022)
Online newspapers have taken centre stage in the media as technology advances, and this has seen newspaper readers moving away from reading printed copies to accessing them on their electronic gadgets. On electronic gadgets, online newspaper readers are also given a platform to make their own comments after reading such copies. It has been observed that in making comments, newspaper readers use pseudonyms. The thrust of this paper therefore is to analyse the meaning and etymology of pseudonyms that are used by commentators on articles in online newspapers in Zimbabwe. The paper also examines the circumstances that give rise to such pseudonyms. In analysing the meaning, the etymology and the circumstances giving rise to such pseudonyms, the discussion revolves around issues to do with history, politics, heroism, and other current affairs of Zimbabwe. The pseudonyms that are analysed here were taken from newspapers that include The Chronicle, The Sunday News, The Herald, Daily News, Newsday, Bulawayo24 and New Zimbabwe that were published between the 1 January and the 31 May 2016. In selecting these newspapers, an effort was made to strike a balance between those that are pro-government and those that explicitly criticise the Zimbabwean government in order to ensure balance regarding politics, history and heroism. A group of pseudonyms from online newspapers was collected and academics were asked to complete questionnaires in order for the researcher to get a broad understanding of the meaning and history of those names. The names were then be analysed on the basis of the thematic pattern(s) that emerged from the information given. The paper concludes by explaining the circumstances that give rise to pseudonyms, with the major conclusion drawn that self-naming in online newspapers is a political statement because most issues in Zimbabwe revolve around politics.